2017
DOI: 10.3350/cmh.2016.0071
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of sorafenib and metronomic chemotherapy for Barcelona Clinic Liver Cancer-stage C hepatocellular carcinoma with poor liver function

Abstract: Background/AimsMetronomic chemotherapy (MET) is frequently administered in comparatively low doses as a continuous chemotherapeutic agent. The aim of this study was to evaluate the feasibility and overall survival (OS) of MET compared to sorafenib for advanced hepatocellular carcinoma (HCC) patients with portal vein tumor thrombosis (PVTT).MethodsA total of 54 patients with advanced HCC and PVTT who had undergone MET were analyzed between 2005 and 2013. A total of 53 patients who had undergone sorafenib therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…On the basis of the inclusion and exclusion criteria of this study, 10 retrospective cohort studies comparing the clinical efficacy and adverse events of HAIC with those of sorafenib for the treatment of BCLC stage C HCCs were finally included. 8 – 17 The flowchart of the search strategy for included studies is shown in Figure 1 . A total of 1,264 patients were included in the study, of whom 505 patients underwent sorafenib treatment and 759 patients underwent HAIC treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of the inclusion and exclusion criteria of this study, 10 retrospective cohort studies comparing the clinical efficacy and adverse events of HAIC with those of sorafenib for the treatment of BCLC stage C HCCs were finally included. 8 – 17 The flowchart of the search strategy for included studies is shown in Figure 1 . A total of 1,264 patients were included in the study, of whom 505 patients underwent sorafenib treatment and 759 patients underwent HAIC treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the clinical effectiveness of HAIC for BCLC stage C HCCs, with response rates ranging from 20.8% to 52%, and the median survival time in complete and partial responders is approximately 40 and 17 months, respectively. 8 – 10 Some previous studies comparing the clinical efficacy of HAIC with that of sorafenib suggested that HAIC was superior to sorafenib for patients with BCLC stage C HCCs. 8 , 12 14 However, some other studies reported conflicting results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We wrote down the torques s i applied by the external forces (magnetic and gravitational) and by the drag force on the aggregate in Eqs. (6) and (7) and the moment of inertia I in Eq. (8):…”
Section: Pump Modulementioning
confidence: 99%
“…The current clinical treatments for liver cancer include surgery, radiotherapy and chemotherapy (1). For patients who miss the optimal timing required for surgery, chemotherapy is the recommended therapy (2). Although the majority of chemotherapy drugs inhibit the excessive proliferation of liver cancer cells, the side effects are may be severe (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%